IDENTIFICATION OF DIFFERENCES OF PRELIMINARY GROUPS OF THE 2020 WORLD HANDBALL CHAMPIONSHIP - Sanja Bajgorić; Muris Đug (Sport Scientific And Practical Aspects, 2025)
The research was conducted with the purpose to identify differences in the efficiency of shooting of the national teams of the preliminary group of the 2020 World Handball Championship. In total, twelve teams were analysed: Montenegro, Serbia, Northern Macedonia, Ucraine, Latvia, Netherlands, Bosnia and Herzegovina, France, Denmark, Russia, Switzerland and Poland, which left the tournament after the preliminary phase and played three games. The analysed variables were: Shots of the positional attack (total number of shots, total successful shots, percentage of shots), Shots with a player more (total number of shots, total successful shots, percentage of shots), Shots with a player less (total number of shots, total successful shots, percentage of shots), Shots from nine meters (total number of shots, total successful shots, percentage of shots). The aim of this research was the identification of differences in the efficiency of shooting in the national teams of the preliminary group of the 2020 World Handball Championship